Nutrition for sport, exercise and performance - Belski, R.; Forsyth, A.; Mantzioris, E. (Allen & Unwin, 2019)
Part 1. The science of nutrition and sport 1. Introduction to sport and exercise - Kane Middleton, Andrew Govus, Anthea Clarke and Adrienne Forsyth 2. Energy for sport and exercise - Matthew Cooke and Sam S.X. Wu 3. Digestion and absorption of macronutrients in sport and exercise - Annie-Claude M. Lassemillante and Sam S.X. Wu 4. Macronutrients - Evangeline Mantzioris 5. Micronutrients and antioxidants . Gina Trakman 6. Translating nutrition: From nutrients to foods - Adrienne Forsyth 7. Dietary assessment - Yasmine C. Probst 8. Introduction to diet planning - Adrienne Forsyth and Tim Stewart Part 2. Nutrition for exercise 9. Macronutrient periodisation - Louise M. Burke 10. Exercise nutrition - Regina Belski 11. Hydration - Ben Desbrow and Christopher Irwin 12. Sports supplements - Michael Leveritt 13. Changing body composition and anthropometry - Patria Hume Part 3. Applied sports nutrition 14. Endurance sports - Gregory Cox 15. Strength and power athletes - Gary Slater and Lachlan Mitchell 16. Team sport athletes - Stephen J. Keenan and Brooke Devlin 17. Weight category and aesthetic sport athletes - Regina Belski 18. Young athletes - Helen O`Connor and Bronwen Lundy 19. Masters athletes - Janelle Gifford and Helen O`Connor 20. Paralympic athletes - Michelle Minehan and Elizabeth Broad 21. Travelling athletes - Shona L. Halson, Georgia Romyn and Michelle Cort 22. Environmental and climate considerations for athletes - Alan McCubbin 23. Gastrointestinal disturbances in athletes - Dana M. Lis and Stephanie K. Gaskell 24. Nutrition support for injury management and rehabilitation - Rebekah Alcock and Greg Shaw 25. Cultural perspectives - Frankie Pui Lam Siu and Evangeline Mantzioris 26. Working with athletes - Anthony Meade